Capitalizing on Collapse: An Analysis of Institutional Single-Family Rental Investors. Issue 6 (November 2021) - Colburn, Gregg; Walter, Rebecca J.; Pfeiffer, Deirdre
A well-documented consequence of the recent foreclosure crisis was a pronounced dislocation in the single-family home market. Large institutional buyers emerged to capitalize on this dislocation. These firms acquired hundreds of thousands of single-family homes to create a pool of single-family rentals (SFRs) in markets across the United States. Existing analyses of institutional investors focus on their aggregate characteristics and associated community effects, showing faster housing recovery in places hard hit by foreclosure but also increases in evictions and home prices. Relatively little is known about individual firms' strategies or how they have evolved over time—knowledge that is critical to understanding the diversity of these actors and establishing causal links to community impacts. We help fill this gap by using quantitative and qualitative data from the corporate filings of publicly traded SFR companies to understand the industry's birth, growth and development, strategies and approaches, and points of differentiation.